Happiness Program in Improving Sleep Quality in Multiple Sclerosis Patients - Reza Masoudi; Kobra Zaheri; Fatemeh Deris; Kamal Solati; Nahid Jivad; Azita Zaheri (Golestan University of Medical Sciences, 2022)
Abstract Background: Since happiness affects the various aspects of human life and is considered as one of the most important psychological needs, achieving it and it effects on the health of the body and soul has always occupied the mind of human beings. The aim of this study was to determine the effect of Forde's happiness program on sleep quality in patients with multiple sclerosis (MS). Methods: This randomized clinical trial study was performed in the MS Society of Shahrekord in 2018. 70 eligible patients with MS were recruited through convenience sampling method and randomly allocated into intervention and control groups equally. The Fordyce Happiness Training Program was conducted in eight sessions in the intervention group. The sleep quality was measured by Pittsburgh Sleep Quality Index (PSQI), before intervention, immediately and three months after the implementation of Fordyce Happiness Program. The data analysis was analyzed using Chi-square, and independent t-test and Fishers exact test for demographic data distribution in intervention and control group, and repeated measures ANOVA for sleep quality in SPSS-16. Results: The findings indicated that total scores of sleep quality of the two intervention (4.61±.052) and control (6.62±.054) groups were not significantly different before the intervention (P=0.05). However, the mean sleep quality scores of intervention and control groups showed a significant difference before, immediately after the intervention with a significant decrease in sleep quality scores over time (F=23.291, P˂0.001). Conclusion: The results of this study demonstrated that the implementation of Fordyce Happiness Training Program in MS patients is a suitable method for improving sleep quality, and if this program continues, they will get better results.